Biaxial flexural strength of 3D-printed 3Y-TZP zirconia using a novel ceramic printer - Zenthöfer, Andreas; Ilani, Ali; Schmitt, Clemens; Rammelsberg, Peter; Hetzler, Sebastian; Rues, Stefan (Clinical oral investigations, 2024)
Objectives  To compare the strength and reliability of 3D-printed 3Y-TZP zirconia manufactured with various printing orientations and staining. Materials and methods  A total of one-hundred cylindrical zirconia specimens were designed and fabricated using 3D printing and processed according to ISO 6872 standards. Of these specimens, 80 were 3D printed using the new ZIPRO-D (ZD) 3D ceramic printer. In this ZD group, 60 specimens were printed in a vertical orientation and were either stained after debinding (ZD1, x-orientation, n = 20) or not stained (ZD2, x-orientation, n = 20; ZD3, y-orientation, n = 20) and the remaining 20 specimens out of n = 80 were printed in a horizontal orientation (ZD4). Further 20 specimens out of the entire sample N = 100 were printed vertically with the CeraFab7500 3D ceramic printer (LC). All completed specimens were loaded until fracture using a universal testing machine. Biaxial flexural strengths and Weibull parameters were computed for the ZD groups and for the LC group. Group and sub-group effects were evaluated using Welch ANOVA (alpha = 0.05). - Results  The mean (standard deviation, SD) biaxial flexural strengths of vertically oriented ZD samples with (ZD1) and without (ZD2/ZD3) staining were 811 (197) and 850 (152) MPa, respectively (p > 0.05). The ZD4 (horizontally printed), 1107 (144) MPa, and LC (1238 (327)) MPa samples had higher mean (SD) flexural strengths than the ZD1-3 specimens. No difference was observed between the ZD4 and LC group (p > 0.05). Weibull moduli were between m = 4.6 (ZD1) and 9.1 (ZD4) in the ZD group and m = 3.5 in the LC group. - Conclusions  All tested 3D-printed zirconia specimens exceeded the flexural strengths required for class 5 restorations according to ISO 6872 standards. While the flexural strengths of zirconia printed using the novel ZD device in the vertical orientation are lower than those of zirconia printed using the LC printer, the ZD printer shows at least comparable reliability. Clinical relevance  3D-printing of zirconia is a new technology in dental application. Based on the presented strengths values, clinical application of 3D-printed zirconia for fixed dental protheses can be recommended.
Gesehen am 22.04.2024